Restoring proximal caries lesions conservatively with tunnel restorations - Chu CH; Mei ML; Cheung C; Nalliah RP (Dove Medical Press, 2013)
Chun-Hung Chu1, May L Mei,1 Chloe Cheung,1 Romesh P Nalliah2 1Faculty of Dentistry, The University of Hong Kong, Hong Kong, People's Republic of China; 2Department of Restorative Dentistry and Biomaterials Sciences, Harvard School of Dental Medicine, Boston, MA, USA Abstract: The tunnel restoration has been suggested as a conservative alternative to the conventional box preparation for treating proximal caries. The main advantage of tunnel restoration over the conventional box or slot preparation includes being more conservative and increasing tooth integrity and strength by preserving the marginal ridge. However, tunnel restoration is technique-sensitive and can be particularly challenging for inexperienced restorative dentists. Recent advances in technology, such as the contemporary design of dental handpieces with advanced light-emitting diode (LED) and handheld comfort, offer operative dentists better vision, illumination, and maneuverability. The use of magnifying loupes also enhances the visibility of the preparation. The advent of digital radiographic imaging has improved dental imaging and reduced radiation. The new generation of restorative materials has improved mechanical properties. Tunnel restoration can be an option to restore proximal caries if the dentist performs proper case selection and pays attention to the details of the restorative procedures. This paper describes the clinical technique of tunnel restoration and reviews the studies of tunnel restorations. Keywords: operative, practice, tunnel preparation, composite, amalgam, glass ionomer